2011
DOI: 10.7205/milmed-d-10-00371
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Veterans With Inflammatory Bowel Disease: Relationship to Health Care Costs and Services

Abstract: Vitamin D deficiency is a global pandemic associated with increased health care costs and could play a role in the pathogenesis and management of inflammatory bowel disease. This study examined vitamin D status in veterans with ulcerative colitis (UC) and Crohn's disease (CD) and assessed its relationship to health care costs and service utilization. Veteran patients (n = 125) with UC or CD and with an available 25-hydroxyvitamin D level were studied. CD patients were more likely to be vitamin D insufficient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…The present study presents two major findings. First, veterans with IBD might not have adequate follow up of vitamin D status, as has been identified in other studies 10 . In addition, and unique to the present study, vitamin D3 was found to be better than D2 in limiting health‐care costs and expenses.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present study presents two major findings. First, veterans with IBD might not have adequate follow up of vitamin D status, as has been identified in other studies 10 . In addition, and unique to the present study, vitamin D3 was found to be better than D2 in limiting health‐care costs and expenses.…”
Section: Discussionsupporting
confidence: 78%
“…Prior studies in veterans show that adequacy of vitamin D follow up is not reached in a significant number of veterans 11 . The work presented here extends similar prior findings in veterans to those with IBD 10 . Failure to test, treat, follow up and attain adequate levels could be the result of multiple factors, including the lack of formal testing guidelines, possible lack of providers' awareness of the vitamin D deficiency pandemic and its serious deleterious health consequences, and the availability of multiple treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 19 cohort studies [18, 34, 38, 41, 50–56, 64, 67, 68, 71, 73, 74, 76, 77], 22 case–control studies [16, 2529, 3133, 35, 42, 43, 46, 49, 5963, 66, 69, 70] and 14 cross-sectional studies [30, 36, 37, 39, 40, 44, 45, 47, 48, 57, 58, 65, 72, 75] were included in the analysis. The total number of participants was 5123 patients and 3033 healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing 25(OH)D 3 levels between CD and UC patients, no differences were found in 8 studies on adult or pediatric patients in basal conditions [ 47 , 54 , 55 , 57 61 ] and in 1 pediatric study on partially vitamin D supplemented patients [ 62 ]. Lower levels in CD compared with UC were found in 5 studies [ 46 , 63 66 ].…”
Section: Vitamin D Status and Related Risk Factors In Ibdmentioning
confidence: 99%
“…Changing methodology and introducing vitamin D reference values as parameter, the importance of vitamin D in IBD has become more convincing. Defining vitamin sufficiency as serum values above 30 ng/mL, vitamin D insufficiency as values between 10/20 and 30 ng/mL, and vitamin deficiency as concentrations below 10 to 15 ng/mL, data from 27 studies from all over the world were available [ 44 , 46 , 52 , 53 , 56 58 , 60 , 61 , 63 , 64 , 69 77 ], 6 of them on cohorts over 100 participants [ 59 , 62 , 66 , 78 80 ], and one with more than 1,000 patients [ 81 ]. In synthesis, vitamin deficiency was found in 8-100% of patients with CD and in 15-60% of patients with UC, vitamin insufficiency in 12-72.3% in CD or in mixed IBD populations and in 7-64% of UC patients.…”
Section: Vitamin D Status and Related Risk Factors In Ibdmentioning
confidence: 99%